Paediatric Rehabilitation Ingredients Measure: a new tool for identifying paediatric neurorehabilitation content. (21st December 2017) - Forsyth, Rob; Young, David; Kelly, Gemma; Davis, Kathy; Dunford, Carolyn; Golightly, Andrew; Marshall, Lindsay; Wales, Lorna
Abstract : Aim: To develop an instrument (Paediatric Rehabilitation Ingredients Measure [PRISM]) for quantitative estimation of contents of interdisciplinary neurorehabilitation for use in studies of relationships between rehabilitation treatment delivered and severity‐adjusted outcomes after acquired brain injury (ABI). Method: The measure was developed using an ingredients–mediators–outcomes model consistent with the International Classification of Functioning, Disability and Health, a literature review, and other current initiatives in the development of rehabilitation treatment taxonomies, with item codevelopment in workshops with rehabilitation professionals. Interrater reliability was assessed in inpatient and residential paediatric rehabilitation settings. Results: Although sometimes an initially unfamiliar perspective on rehabilitation practice, PRISM's acceptability amongst professionals was excellent. Internal consistency of scores was sometimes an issue for users unfamiliar with the tool; however, this improved with practice and interrater reliability (assessed by Kendall's W ) was good. The tool was felt to have particular value in facilitating interdisciplinary communication and working. Modifications to the design of the tool have improved internal consistency. Interpretation: PRISM supports identification of the 'active ingredients' of an interdisciplinary rehabilitation package and facilitates interdisciplinary communication. It also has potential as a research tool examining relationships between rehabilitation delivered and severity‐adjusted outcomes observed after paediatric ABI. What this paper adds: Identifying contribution of rehabilitation to outcomes after acquired brain injury requires quantification of rehabilitation 'dose' and 'content'. Previous approaches to 'parsing' of rehabilitation dose and content may have overemphasized one‐to‐one sessions with therapists. We present a novel, holistic tool for identification of ingredients of an interdisciplinary rehabilitation package. It supports interdisciplinary communication and has potential as a research tool. What this paper adds: Identifying contribution of rehabilitation to outcomes after acquired brain injury requires quantification of rehabilitation 'dose' and 'content'. Previous approaches to 'parsing' of rehabilitation dose and content may have overemphasized one‐to‐one sessions with therapists. We present a novel, holistic tool for identification of ingredients of an interdisciplinary rehabilitation package. It supports interdisciplinary communication and has potential as a research tool. This article is commented on by Autti‐Rämö on page222 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations. Video Podcast:https://www.youtube.com/watch?v=QW6ZwY1gacs&t=2s